2021
DOI: 10.1055/s-0041-1731137
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colistin Resistance in Carbapenem Resistant Enterobacteriaceae by Reference Broth Microdilution and Comparative Evaluation of Three Other Methods

Abstract: Objective Challenges in susceptibility testing of colistin along with increase in the prevalence of colistin-resistant carbapenemase-producing Enterobacteriaceae (CRE) pathogens needs addressal. Evaluation of user-friendly methods is necessary as an alternative to broth microdilution (BMD), the reference susceptibility testing method, for routine implementation in diagnostic clinical microbiology laboratories. Genotypic detection of the plasmid-mediated colistin resistance is also needed for infection control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…Klebsiella spp were the most frequent CRGNB isolates (36.1%) followed by Escherichia coli (32.9%), Pseudomonas aeruginosa (12.9%), Acinetobacter spp (8.4%), Enterobacter spp (5.8%) and Citrobacter spp (3.9%). Matching with carbapenem resistance rates (54.5% and 55.8%) in previous studies 17,4 . On the contrary, lower rates (18.5% and 23.1%) were reported in other studies 18-19 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Klebsiella spp were the most frequent CRGNB isolates (36.1%) followed by Escherichia coli (32.9%), Pseudomonas aeruginosa (12.9%), Acinetobacter spp (8.4%), Enterobacter spp (5.8%) and Citrobacter spp (3.9%). Matching with carbapenem resistance rates (54.5% and 55.8%) in previous studies 17,4 . On the contrary, lower rates (18.5% and 23.1%) were reported in other studies 18-19 .…”
Section: Discussionsupporting
confidence: 66%
“…Intensive Care Units were the main source of these samples (50.32%), followed by surgical departments (18.71%), nursery (14.84%), medical departments (9.03 %) and burn unit (7.1%). Kra et al 17 reported the same observations. While, Saed et al mentioned that tracheal aspirate was the main source of CRGNB isolates 20 .…”
Section: Discussionsupporting
confidence: 56%
“…Our results demonstrated that, fosfomycin was the most effective antibiotic (93.5%) against CPKp followed by tigecycline (92.5%), gentamicin (90.3%), amikacin (86.0%), trimethoprim-sulfamethoxazole (81.7%), colistin (81.7%) and then β-lactam/βlactamase inhibitors (76.3%). That is higher than the susceptibility in Kar et al 26 study who found that, netilmicin, amikacin, gentamicin, trimethoprimsulfamethoxazole, piperacillin-tazobactam and fosfomycin were the most effective against CRE by only 23%, 21%, 20.5%, 15.5%, 8.5% and 5.5% respectively. And around the susceptibility pattern of Ajlan et al 19 study, who detected that the most effective drug against CRGNB isolates was colistin (72.3%), followed by ceftazidime-avibactam (67.7%), then tigecycline (63.2%).…”
Section: Table (5): Antibiotic Susceptibility Of Cpkp In Relation Tomentioning
confidence: 70%
“…In our study, we evaluated a larger number of strains (n=309) than previous studies, where the number of strains analysed ranged from 75 to 271 isolates [9,11,14,15,20]. Overall, the drop test met the FDA-established criteria for assessing antimicrobial susceptibility [18].…”
Section: Discussionmentioning
confidence: 99%